Association of professional identity, gender, team understanding, anxiety and workplace learning alignment with burnout in junior doctors: a longitudinal cohort study. Issue 12 (27th December 2017) - Monrouxe, Lynn V; Bullock, Alison; Tseng, Hsu-Min; Wells, Stephanie E
Abstract : Objectives: To examine how burnout across medical student to junior doctor transition relates to: measures of professional identity, team understanding, anxiety, gender, age and workplace learning (assistantship) alignment to first post. Design: A longitudinal 1-year cohort design. Two groups of final-year medical students: (1) those undertaking end-of-year assistantships aligned in location and specialty with their first post and (2) those undertaking assistantships non-aligned. An online questionnaire included: Professional Identity Scale, Team Understanding Scale, modified Hamilton Anxiety Rating Scale and modified Copenhagen Burnout Inventory. Data were collected on four occasions: (T1) prior to graduation; (T2) 1 month post-transition; (T3) 6 months post-transition and (T4) 10 months post-transition. Questionnaires were analysed individually and using linear mixed-effect models. Setting: Medical schools and postgraduate training in one UK country. Participants: All aligned assistantship (n=182) and non-aligned assistantship students (n=319) were contacted; n=281 (56%) responded: 68% (n=183) females, 73% (n=206) 22–30 years, 46% aligned (n=129). Completion rates: aligned 72% (93/129) and non-aligned 64% (98/152). Results: Analyses of individual scales revealed that self-reported anxiety, professional identity and patient-related burnout were stable, while team understanding, personal and work-related burnout increased, all irrespective of alignment. Three linear mixed-effect models (personal, patient-related and work-related burnout as outcome measures; age and gender as confounding variables) found that males self-reported significantly lower personal, but higher patient-related burnout, than females. Age and team understanding had no effect. Anxiety was significantly positively related and professional identity was significantly negatively related to burnout. Participants experiencing non-aligned assistantships reported higher personal and work-related burnout over time. Conclusions: Implications for practice include medical schools' consideration of an end-of-year workplace alignment with first-post before graduation or an extended shadowing period immediately postgraduation. How best to support undergraduate students' early professional identity development should be examined. Support systems should be in place across the transition for individuals with a predisposition for anxiety.